Penerapan Sistem Inferensi Fuzzy untuk Menentukan Jumlah Pembelian Produk Berdasarkan Data Persediaan dan Penjualan dengan Menggunakan Metode Mamdani (Studi: Kasus RM Habibi) - Hidayati, Nani; Kasini, Kasini; Permata, Aprilia (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
RM Habibi is a restaurant business that serves dishes to buyers and provides a place to enjoy the meal, as well as determining food and service costs. Although restaurants generally serve on site, there are also those that provide take away and delivery services as a form of service to buyers. Restaurants usually specialize in the types of food they provide and are their best sellers. Inventory problems are a problem that buyers always face. Inventory is needed because demand patterns are basically irregular. Inventory is carried out to ensure certainty that when needed the product is available. Fuzzy logic is one of the components that make up soft computing. The application of the fuzzy inference system (FIS) with the mamdani method in the Demand, Supply and Sales prediction system can be concluded that the use of fuzzy logic can be used to predict demand, inventory and totals at the Habibi Restaurant. And test results with real data and surveys show results with a conformity level of up to 90%.